PENGARUH LINGKUNGAN KERJA NON FISIK DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KARYAWAN BAGIAN PENJUALAN PT. MITRABUANA CITRA ABADI – FORD MITRA SEMARANG) - Dita Tri Pamungkas; Ngatno Ngatno (Universitas Diponegoro, 2017)
Competition in automotive industry has highly improved over the time. Advancement in technology and professional human resource are required to maintain sustainability of a company. Human resources have a vital role in a company as planner, director, and performer in every operational activity. This research is conducted to discover how non-physical environment and work stress are influencing working productivity of sales employee in PT. Mitrabuana Citra Abadi- Ford Mitra Semarang by using working motivation as intervening variable. Population in this research is all of sales employee in Ford Mitra Semarang with 34 respondents as the sample. Sampling which is used in this research is saturated sampling. Analyzing technique used is quantitative technique by examining validity, reliability, correlation’s coefficient, determination’s coefficient, simple and multiple regression analysis, signification test (t’s test and f’s test), and sobel test. The result of this research show that non-physical working environment’s variable and working motivation influence working productivity’s variable either partially or simultaneously. According to Sobel test, it can be inferred that non-physical working environment has positive influence on working productivity through working motivation with mediation coefficient’s value 0,108 which is categorized as partial mediation. Moreover, work stress has negative influence on working productivity through working motivation with mediation coefficient’s value 0,103 which is categorized as partial mediation. The advice which can be given from this research is that the company requires improvement in employee’s working motivation to which it increases their productivity. In addition, the company has to create a better relationship with the employee in order to make a more concussive working environment. Last but not least, awarding the employee might be needed to appreciate their great work performance.